Medicine and Humanitarian Emergency / Mohamad Ikhsan Selamat and Mohammed Fauzi Abdul Rani - Selamat, Mohamad Ikhsan; Abdul Rani, Mohammed Fauzi (Universiti Teknologi MARA Cawangan Selangor, 2017)
A humanitarian emergency is an event that signifies a critical threat to the health and wellbeing of a community in an area and arises when vulnerable populations are unable to withstand the adverse consequences [1]. Invariably the poor people are mostly affected, especially among them are the children, disabled, women who are pregnant or nursing, the migrants, and the people who are displaced from either man-made or natural disasters. In Malaysia similar needs tend to emerge among the vulnerable populations following natural disasters such as major flooding, as the one that affected Kelantan in 2014, and another plight concerns a large number of migrants within our midst from man-made emergencies predominantly armed conflicts in Myanmar or southern Philippine. Categorization of any humanitarian emergency is challenging but for logistical reasons are necessary. The focus of intervention however remains the same that is to save lives and reduce suffering through meeting humanitarian needs. The way in which such needs are met depends on the specific emergency and prevailing circumstances such as the extent of violence and loss of life, people's displacements, physical damage to infrastructure, the size of help needed including the absence or presence of political will, and the risks all above pose to volunteers.